Wage Gaps between Native and Migrant Graduates of Higher Education Institutions in the Netherlands - Masood Gheasi; Peter Nijkamp; Piet Rietveld (Institute for the Study of Labor (IZA), 2015)
In the Netherlands the share of immigrants in the total population has steadily increased in recent decades. The present paper takes a look at wage differences between natives and migrants who are equally educated. This reduces potential skills biases in our analysis. We apply a Mincer equation in estimating the wage differences between natives and migrants. In our study we analyze only young graduates, so that conventional human capital factors cannot explain the differences in monthly gross wages. Therefore, we focused on "otherness" factors, such as parents' roots to find an alternative explanation. Our empirical results show that acquiring Dutch human capital, Dutch-specific skills, language proficiency, and integration in the long-term (second-generation with non-OECD background) are not sufficient to overcome wage differences in the Dutch labor market, especially for migrants with parents from non-OECD countries.
Keywords: F22; I2; 330; immigration; education; wage